Management training approaches in the Malaysian hotel industry - Zainal, Artinah; Adullah, Iskandar (Tourism Educators Association of Malaysia, 2004)
The objective of this study was to develop a framework for identification of the most appropriate, valuable and practical aspects of management training approaches, such as trainer-directed training (TDT) and self-directed training (SDL) to be adopted by the hotel organizations. To accomplish this objective, key aspects were identified through an Expert Survey. This study sorted the opinions of industry professionals namely training managers and human resources managers from four and five-stars rating hotels in the vicinity of Kuala Lumpur and Selangor. The study was conducted in Two Phases; which is the preliminary interviews and Delphi Technique with three iterations to 20 industry professionals. Key aspects of management training approaches were importance of TDT and SDL and improvement for management training. All key aspects receiving two-third votes in the ‘higher level agreement categories’ (Likert-type scale 4=agree and 5=strongly agree) that were considered as important or essential were included in the framework. The Delphi panel of experts identified 44 key aspects that were considered as emerging consensus. They were 35 aspects on management training approaches and 9 aspects on future improvement for hospitality management training and development. The results of the findings concluded that training approach or instructional design such as TDT and SDL might be incorporated in activities of hospitality management trainees. TDT and SDL being two polar extreme on continuum; namely objectivism and constructivism, are able to increase trainees morale and motivation in their own way and may be adopted for different stages of training phases. It was also concluded that with the combined instructional system design of trainer-directed and learner-controlled in the industry, the hospitality practitioners and institutions of higher learning with hospitality degree program could prepare personnel qualified to improve hospitality organizations in the future.